EFEKTIVITAS PELATIHAN PENGELOLAAN KECEMASAN TERHADAP KECEMASAN BERKOMPETISI PADA ATLET BULU TANGKIS REMAJA - Devi Jatmika; Linda Linda (Universitas Bunda Mulia, 2016)
Badminton is one of popular sports and has resulted many achievements in Indonesia. The effort of Indonesian Badminton Union (Persatuan Bulutangkis Seluruh Indonesia) to regenerate young talented players is the shuttletime program in which they collaborate with schools to teach badminton. Competition anxiety has become a psychological factor that hinders players’ performance. Amateur athletes are more easily feel anxious compare with professionals’ athletes because of the lack of experiences in competition and emotion management. Anxiety reduction training sometimes is not a priority as happened at UNJ badminton club. The aime of this research is to identify the effectivity of anxiety management training towards competition anxiety among UNJ adolescents’ athletes. Anxiety training that gave to them was relaxation technique and self talk. This research was experimental research which is one group design. The treatment was anxiety training, the anxiety tes was given before and after training. The results revealed t score= 0.201 with sig 0.842 > 0.05, mean the anxiety treatment still could not decreased anxiety. The intensity for practicing anxiety management whereas there were participants did not do the technique that had been taught and the lack encouragement from the coach to the team before competition were some of variables that made the training was not effective for the badminton athletes. Keywords: anxiety management; competition anxiety; badminton athletes; adolescent.